2012
DOI: 10.1111/j.1471-4159.2011.07637.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neuronal plasticity and elevated endogenous sAPPα levels in mice over‐expressing MMP9

Abstract: J. Neurochem. (2012) 121, 239–251. Abstract Evidence accumulating during the past few years points to a significant role of matrix metalloproteinase 9 (MMP9) enzymatic activity in synaptic plasticity and cognitive processes. We have previously demonstrated that MMP9 is involved in receptor‐mediated α‐secretase‐like cleavage of APP in vitro, resulting in increased secretion of sAPPα, the soluble N‐terminal product of the non‐amyloidogenic pathway known to be involved in neuronal plasticity and memory formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 38 publications
3
45
0
4
Order By: Relevance
“…The generation of 5XFAD and TgMMP-9, respectively, has been previously reported 28, 48 . Briefly, 5XFAD mice co-express and co-inherit FAD mutant forms of human APP [Swedish (K670N, M671L), Florida (I716V) and London (V717I) mutation] and presenilin-1 (M146L; L286V) transgenes under the transcriptional control of the neuron-specific mouse Thy-1 promoter, whereas TgMMP-9 mice express the wild-type human pro-MMP-9 sequence under the transcriptional control of the neuron-specific promoter platelet-derived growth factor (PDGF)-β.…”
Section: Methodsmentioning
confidence: 90%
“…The generation of 5XFAD and TgMMP-9, respectively, has been previously reported 28, 48 . Briefly, 5XFAD mice co-express and co-inherit FAD mutant forms of human APP [Swedish (K670N, M671L), Florida (I716V) and London (V717I) mutation] and presenilin-1 (M146L; L286V) transgenes under the transcriptional control of the neuron-specific mouse Thy-1 promoter, whereas TgMMP-9 mice express the wild-type human pro-MMP-9 sequence under the transcriptional control of the neuron-specific promoter platelet-derived growth factor (PDGF)-β.…”
Section: Methodsmentioning
confidence: 90%
“…Notably, MMP-9 has been shown to mediate morphological changes in dendritic spines after synaptic stimulation (see above), and it might be potentially involved in dendritic spine pathology in schizophrenia. Furthermore, Fragkouli et al 44 and Gkogkas et al 45 reported an increase in dendritic spine density in the hippocampus and cortex in transgenic mice that overexpress MMP-9.…”
Section: Mmp-9 In Schizophreniamentioning
confidence: 98%
“…MMP-9, which is expressed in an activity-dependent manner, is important for normal synaptic plasticity, but it also has α-secretase activity. This notion is supported by observations that MMP-9-overexpressing transgenic mice have elevated levels of sAPPα, greater LTP in the hippocampus, and enhanced memory (Fragkouli et al, 2012). Furthermore, MMP-9 overexpression in a mouse model of AD reduced the level of Aβ and its oligomers in the brain and restored learning deficits to the levels of wildtype animals (Fragkouli et al, 2014).…”
Section: Expression Of Metzincins In Alzheimer’s Diseasementioning
confidence: 80%